Invertebrate-mediated dispersal plays an important role in shaping the current distribution of a herbaceous monocot - Chen, Yong-Sheng; Zeng, Chun-Xia; Muellner-Riehl, Alexandra N.; Wang, Zhi-Heng; Sun, Lu; Schinnerl, Johann; Kongkiatpaiboon, Sumet; Kadota, Yuichi; Cai, Xiang-Hai; Chen, Gao (Journal of BiogeographyJournal of Biogeography, 2021)
Abstract Aim Invertebrate-mediated dispersal has previously been proposed to promote angiosperm diversification and distribution. However, little is known about the specific impact of invertebrate-mediated dispersal on the biogeography and current distribution of plants. We aim to infer the influence of vespicochorous (hornet) and myrmecochorous (ant) dispersal on the historical biogeography of herbaceous monocot species. Location Southeast Asia, East Asia, Australia, North America. Taxon Family Stemonaceae. Method We sampled ca. 75% of the species diversity in Stemonaceae (28 out of 37 species), covering the entire distribution range of the family, to reconstruct the biogeographic history of this family. Using phylogenetic logistic regression analyses, we then tested the relationship between dispersal modes and geographic distributions. Results Stemonaceae originated on the Asian mainland during the late Cretaceous and then dispersed to North America, the western Malay Archipelago and eastern Malay Archipelago and Australia between the late Cretaceous and Pliocene. Geographical ranges of ant- versus hornet-dispersed Stemonaceae species are significantly different, with vespicochorous species having broader distribution ranges than myrmecochorous species. Main conclusions Invertebrate-mediated dispersal in Stemonaceae may promote narrow endemism and play an important role in shaping the current distribution of species. Most lineages dispersed by ants failed to cross biogeographic barriers and exhibit limited range expansion overland. Vespicochorous lineages were able to cross oceanic barriers and occupy larger continental areas and/or occur on oceanic islands.
Keywords: biogeography; endemism; myrmecochory; Pandanales; Stemonaceae; vespicochory